ТЕХНОЛОГІЇ САМОМЕНЕДЖМЕНТУ СТУДЕНТІВ ЯК ОСНОВИ ЕФЕКТИВНОГО ДИСТАНЦІЙНОГО НАВЧАННЯ - Kaschuck, Kateryna (Zhytomyr Ivan Franko State University, 2021)
The urgency of the problem of distance education development is caused by the fact that in modern conditions the requirements for specialists are radically changing. At the same time, the central place is not the use of previously acquired knowledge, but the generation and implementation of new ideas, which dictates new requirements for training. In this regard, lifelong learning becomes increasingly necessary, acquires new forms and meanings. Today, advances in information technology and telecommunications allow the development of distance learning as a kind of continuing education that accompanies the information society, because it forms a comprehensively developed personality, able to navigate in the information environment. The pandemic forced universities to switch to e-Learning in a force majeure mode, which served as a powerful impetus for the accelerated arming of universities with resources that allow them to effectively practice online and blended learning. In these conditions, it became possible to implement a student-centered educational paradigm. However, this is hindered by the problem of the student's lack of self-organization and self-motivation skills, the ability to take responsibility for their own learning and development. This problem is gaining more and more theoretical and practical importance. The purpose of the work is to substantiate that courses such as self-management and time management contribute to the formation of competencies in the field of goal-setting, planning, self-organization, self-control and self-motivation, and, therefore, in the context of the implementation of student-centered pagadigma, they should serve as preliminary study for e-Learning. For this, the article provides a review of the "Time Management" content course in relation to the task of developing proactivity and the student’s ability to systematically and productively independent work.